(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This scientific article provides an in-depth analysis of the role of applied and singular economy theories in modern economic processes and the scientific and theoretical differences between them. While applied economics is aimed at solving real economic problems, singular economics is based on a fundamental change in economic processes through technological revolution and digital transformation. Based on the concepts of Bobojonova Zarnigor (2023) and other leading scientists, the similarities and differences of these two approaches are systematically highlighted in two separate tables. The article analyzes the potential of the singular economy to increase economic competitiveness through human capital, innovation, and artificial intelligence. Strategic proposals for the implementation of these theories in practice in the conditions of Uzbekistan are also developed.